The Effect of Teaching According To Systemic Thinking Skills on The Achievement of Literary Criticism Among Students of The Arabic Language Department (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify the effect of teaching according to systemic thinking skills on the acquisition of modern literary criticism subject to Arabic language departments in basic education colleges. To achieve the goal of the research, the researcher relied on an experimental design with partial control, which is the design of the experimental and control groups with a post-test. He chose The researcher intentionally sampled the College of Basic Education at the University of Kufa for his research, and it amounted to (99) male and female students, from the fourth grade, divided into two groups that were chosen randomly. Division (A) represented the experimental group with (49) male and female students, while Division (B) represented a triangle. The control group consisted of (50) male and female students. The researcher rewarded the students of the two research groups in the two variables: grades in the literary criticism subject in the previous stage, and a measure of mental motivation. As for the research tool, it is an achievement test prepared by the researcher according to Bloom’s six levels (remembering, understanding, application, analysis, synthesis, evaluation) according to what The test map produced it, as it included (50) items, (40) multiple-choice items, and (10) items of specific essay questions. The researcher verified the validity and reliability of the test, and extracted the difficulty factor of its items and their discriminatory power after applying it to An appropriate statistical sample, and presented to a group of arbitrators. After the end of the experiment period, the researcher applied the test to the students of both research groups, and after processing the data using a number of appropriate statistical methods, the researcher concluded that there was a statistically significant difference at the level (0.05) in favor of the experimental group. In light of the results of the research, the researcher concluded that teaching according to systemic thinking skills contributes to raising the level of achievement in literary criticism. He also recommended activating these skills in teaching other branches of the Arabic language